Lived experiences of nurses in the care of patients with COVID-19: A study of hermeneutic phenomenology - Fatemah Moghaddam-Tabrizi; Roghieh Sodeify (Wolters Kluwer Medknow Publications, 2021)
Background: Nurses are at the forefront of caring for patients with COVID-19 and face a life-threatening risk to perform their duties. The complexity of disease conditions such as emerging disease may interfere with good nursing care and holistic care. The aim of this study is to reveal the lived experiences of nurses in the care of patients with COVID-19. Materials and Methods: This qualitative study was conducted in Khoy, Iran from March 2020 to May 2020. Fourteen nurses underwent in-depth semi-structured interviews at COVID-19 Central Hospital. All interviews were recorded, transcribed, and analyzed. Diekelmann's hermeneutic phenomenological approach was used to analyze and interpret the data. MAXQDA software version 2007 was used to manage and organize the data. Results: After extensive analysis and reflection, four main themes emerged, including staying in an ethical dilemma, emotional turmoil, response to professional commitments, and seeking help. Conclusions: The results of this study provided basic information about the lived experiences of nurses in different dimensions. Nursing managers need to be aware of these needs and expectations and provide a variety of programs and strategies not only to support nurses but also to ensure the quality of patient care.